BALANGAY a sustainable floating village for low-income families in Manila Bay - Olegario, James Edward M. (College of Architecture, University of the Philippines Diliman, 2022)
The growth of slum dwellings is alarming for urban areas including Metro Manila. With far-flung or costly housing projects paired with the lack of livelihood opportunities, low-income residents flock towards cheap but hazardous and unhealthy slum communities. This project aims to provide an alternative architectural solution to housing for the urban poor, ensuring the safety, affordability, and opportunity for growth of its residents. Specifically, it explores the potential of a sustainable floating development guaranteeing the livability of the residents through the ocean's abundant resources. The study examines floating structures, their construction, and their effects on the environment and dwells on the principles of sustainability in practices, architecture and urbanism. The resulting architectural solution was a floating development achieving sustainability through resilient construction, livelihood opportunities, renewable resources, affordability and upgradeability, an improvement over low-income residents' previous slum dwelling. Green practices are encouraged by the project to its residents through technologies generating and recycling electrical and water resources, preventing adverse effects brought to the waters and atmosphere. The project focuses on integrating floating concepts, urban theories and green technologies to the urban development in achieving sustainability, resiliency, imageability and responsiveness. Further studies are needed to explore the potential of floating urban developments.